Revision of the species confused with “Nereis falsa” de Quatrefages, 1866 (Annelida, Nereididae) - Salazar-Vallejo, Sergio I.; De León-González, Jesús Angel; Conde-Vela, Victor M. (European Journal of Taxonomy, 2021)
Nereis falsa de Quatrefages, 1866 has been regarded as a cosmopolitan species, and several species described from different localities have been regarded as junior synonyms of N. falsa. The present study is an attempt to resolve the taxonomic confusion in N. falsa, which seems to contain several distinct species due to previous inappropriate synonymy, widely distributed in the Atlantic and eastern Pacific Oceans. For this purpose, the authors first propose the resurrection of the synonymy of N. falsa with Hediste diversicolor that was concluded during the 19th century but disregarded later. After the fixation of the identity of N. falsa sensu stricto, the authors re-evaluate the proper taxonomic status of species which have previously been confused with N. falsa. Type, topotype and non-type specimens were examined; most species are redescribed, and others are reinstated. Nereis splendida Grube, 1840 is a valid Mediterranean species, and a neotype is proposed; it includes the Mediterranean populations of what is currently regarded as N. falsa. Consequently, N. falsa is transferred to Hediste Malmgren, 1867, and some taxonomic comments are added for the latter genus and a key to species is also included. Nereis callaona Grube & Kröyer in Grube, 1857, N. marginata Grube & Örsted in Grube, 1857 and N. riisei Grube & Örsted in Grube, 1857 are restricted to tropical American shores and are all redescribed. Nereis pelagica lunulata Ehlers, 1901, formerly regarded as a junior synonym of N. falsa by Fauvel (1941), is redescribed and elevated in rank to species level. Nereis lucipeta Ehlers, 1908, formerly regarded as a junior synonym of N. splendida by Ehlers (1913) and of N. falsa by Fauvel (1919), is reinstated. Nereis occidentalis Hartman, 1945 is also redescribed. Furthermore, N. ambigua Treadwell, 1937, formerly regarded as a junior synonym of N. riisei by Monro (1933), deserves to be reinstated. Western Africa specimens recorded as N. falsa are newly described as N. mezianei sp. nov.